Insilico docking analysis of mangrove-derived compounds against breast cancer protein (BRCA1) - Sunilkumar Sahu, Senthil Raja, P. Kathiresan, K. (International Multidisciplinary Research Journal, 2011)
Breast cancer is the second leading cause of cancer death in women only next to lung cancer. In normal cells, BRCA1 and BRCA2 (breast cancer susceptibility gene 1 and breast cancer susceptibility gene 2) ensure the stability of DNA and also prevent uncontrolled cell growth. Mutation of these genes is linked to the development of hereditary breast and ovarian cancers. Considering the lacunae of reliable and potential drugs to cure the life threatening breast cancer, the present study has focused on molecular computational analysis to identify the potential compounds, derived from mangrove ecosystem, which can block the mutated gene (BRCA1) responsible for the breast cancer. Six compounds were tested against the carcinogenic protein. The 3D crystal structure of the protein was retrieved from protein data bank (PDB) and the protein binding sites of the test compounds were identified. The results revealed that among six compounds, triterpenoid, stigmasterol and pyrethrin were found efficient in destroying the protein (BRCA1) responsible for breast cancer.